EVALUASI KINERJA MELALUI PELATIHAN DAN PENGEMBANGAN SDMPADA PT. GLOBAL TEKNOLOGI KREASINDO - Sudianto Sudianto (EQUILIBIRIA, 2020)
The purpose of this study was to analyze the effect of training, HR development on employee performance at PT. In this research the variables discussed are the dependent variable, namely job training and human resource development and free variables, namely employee performance variables. This research was conducted using quantitative research methods. Data collection methods were used using the Slovin formula, a sample of 67 people given to employees. who has a supervisory position down at Pt Global Teknologi Kreasindo. The data is processed using SPSS software version 20.0 for Windows. The results showed that HR training and development had no significant positive effect on employee performance. Both HR Training and Development both have a positive influence on employee performance at PT. Global Teknologi Kreasindo.